The social network index and its relation to later-life depression among the elderly aged ≥80 years in Northern Thailand - Aung MN (Dove Medical Press, 2016)
Myo Nyein Aung,1 Saiyud Moolphate,2 Thin Nyein Nyein Aung,3 Chitima Katonyoo,2 Songyos Khamchai,4 Pongsak Wannakrairot1 1Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 2Department of Public Health, Chiang Mai Rajabhat University, Chiang Mai, Thailand; 3Department of Public Health, Juntendo University School of Medicine, Tokyo, Japan; 4Chiang Mai Provincial Health Office, Chiang Mai, Thailand Background: Having a diverse social network is considered to be beneficial to a person’s well-being. The significance, however, of social network diversity in the geriatric assessment of people aged ≥80 years has not been adequately investigated within the Southeast Asian context. This study explored the social networks belonging to the elderly aged ≥80 years and assessed the relation of social network and geriatric depression. Methods: This study was a community-based cross-sectional survey conducted in Chiang Mai Province, Northern Thailand. A representative sample of 435 community residents, aged ≥80 years, were included in a multistage sample. The participants’ social network diversity was assessed by applying Cohen’s social network index (SNI). The geriatric depression scale and activities of daily living measures were carried out during home visits. Descriptive analyses revealed the distribution of SNI, while the relationship between the SNI and the geriatric depression scale was examined by ordinal logistic regression models controlling possible covariants such as age, sex, and educational attainment. Results: The median age of the sample was 83 years, with females comprising of 54.94% of the sample. The participants’ children, their neighbors, and members of Buddhist temples were reported as the most frequent contacts of the study participants. Among the 435 participants, 25% were at risk of social isolation due to having a “limited” social network group (SNI 0–3), whereas 37% had a “medium” social network (SNI 4–5), and 38% had a “diverse” social network (SNI ≥6). The SNI was not different among the two sexes. Activities of daily living scores in the diverse social network group were significantly higher than those in the limited social network group. Multivariate ordinal logistic regression analysis models revealed a significant negative association between social network diversity and geriatric depression. Conclusion: Regular and frequent contact with various social contacts may safeguard common geriatric depression among persons aged ≥80 years. As a result, screening those at risk of social isolation is recommended to be integrated into routine primary health care-based geriatric assessment and intervention programs. Keywords: aging, gerontology, psychogeriatrics, sociology of aging, community, Southeast Asia, Chiang Mai